Camino winds - Grisham, John (New York : Doubleday, 2020)
"Just as Bruce Cable's Bay Books is preparing for the return of bestselling author Mercer Mann, Hurricane Leo veers from its predicted course and heads straight for the island ... The hurricane is devastating: homes and condos are leveled, hotels and storefronts ruined, streets flooded, and a dozen people lose their lives. One of the apparent victims is Nelson Kerr, a friend of Bruce's and an author of thrillers. But the nature of Nelson's injuries suggests that the storm wasn't the cause of his death: he has suffered several suspicious blows to the head"--Dust jacket flap.
"A novel"--Jacket.
Sequel to: Camino Island
Keywords: Hurricanes -- Fiction; Bookstores -- Fiction; Antiquarian booksellers -- Fiction; Authors -- Fiction; Murder for hire -- Fiction; Florida -- Fiction; Thrillers (Fiction); Detective and mystery fiction